Randomized Trial of Irrigation and Curetting for Cerumen Removal in Young Children - Timothy R. Shope; Cathy P. Chen; Hui Liu; Nader Shaikh (Frontiers Media S.A., 2019)
Objectives: To gather preliminary data on the effectiveness and feasibility of cerumen removal using three irrigation methods and a metal curette in young children.Study design: Pilot study conducted as a randomized clinical trial of well and ill children age 6 months to 6 years with ≥25% cerumen occlusion in at least one ear. Children were stratified by age and randomized to one of four methods of cerumen removal: syringe with attached angiocath tubing, Elephant Ear Washer Bottle System®, OtoClear® Spray Wash Kit, or metal curette. Clinicians, blinded from treatment assignment, assessed the degree of cerumen occlusion before and after the procedure. Outcomes included reduction in cerumen occlusion, successful removal, time until completion and parental satisfaction. Rules for stopping procedures were established a priori.Results: Thirty-eight children underwent procedures (59 ears). There were no significant differences in reduction in cerumen and successful removal among the methods. Overall, 36 (61%) of 59 of procedures were successful. The syringe with angiocath tubing took the most time (P = 0.04) and resulted in the most stopped procedures (P < 0.01). Parental satisfaction scores were not significantly different.Conclusions: Irrigation methods performed comparably to cerumen removal with curette; the SA method had drawbacks. Irrigation can be performed by non-clinicians, which is potentially a significant advantage. (Clinical trial registration: http://www.isrctn.com/ISRCTN74402562).